Analysis of the profitability performance and state effect in base industry through multilevel regression - Moori, Roberto Giro; Moori, Renata Akemi; Moori, Tatiana Mayumi; Nakatani, Leonardo Daigo (Revista Gestão da Produção Operações e Sistemas, 2008)
The aim of this study is to analyze the hierarchical influence of federal units (or state as a political entity) and industrial sectors on the profitability performance in base companies. For such, a sample of 543 companies was used from 11 industrial sectors in 24 Brazilian states. The data collected were submitted to a three-level model of multilevel regression analysis to detect variance among industrial sectors,. Research results showed that the industrial sector does not explain company profitability performances at a statistically significant level (a = 0,05). The state, as a political entity, on average, had positive and significant influence in the mid-south region, considering the company profitability index. Due to these results, it can be concluded that public politics focused on base industries is still important and essential for developing other federal units in Brazil, thus avoiding an unbalanced region or its fragmentation as a result of competition between stronger economy regions. Keywords: Profitability, multilevel regression, base industry.